Synthesis, Characterization, and In Silico Evaluation of Pyrazole- 1,3,4-Oxadiazole Scaffolds as Aurora Kinase Inhibitors - Sampath Kumar,; Jagadeshwar Vannada, (The Bioscan, 2025)
A robust and efficient synthetic strategy for a series of new pyrazole-linked 1,3,4-oxadiazole scaffolds was synthesized and structurally characterized 1H-NMR, 13C NMR, IR and ESI-MS. Comprehensive insilico studies were conducted to assess the inhibitory potential of all synthesized molecules towards aurora kinase, a critical regulator of cell cycle progression. Molecular docking of the synthesized derivatives revealed that molecules 4g and 4h exhibited superior Glide scores, glide energy, human oral absorption, comparable to clinically relevant aurora kinase inhibitor danusertib. Markedly, the conserved interaction with the key active site residues was consistently observed across the most active molecules and danusertib, underscoring its pivotal role in aurora kinase inhibition. Collectively, these findings highlight molecules 4g and 4h as promising lead molecules for further development as potent aurora kinase inhibitors with potential anti-cancer applications.